Academic research achievements in the geography of tourism at the Department of Regional Geography and Tourism, Maria Curie-Skłodowska University, Lublin: Didactic and practical applications - Skowronek, Ewa; Brzezińska-Wójcik, Teresa; Świeca, Andrzej; Jóźwik, Marta J. (Turyzm/Tourism, 2017)
The present paper is an attempt to assess academic research achievements in the field of the geography of tourism and their didactic and practical applications. The study method was a review of academic articles and archival compilations as well as materials collected in the department.